MOTHER’S INTERNAL FACTORS RELATIONSHIP TO VERBAL ABUSE BEHAVIOR AMONG SCHOOL-AGE DURING COVID-19 PANDEMIC - Nova Alvionita; Rizki Fitryasari; Iqlima Dwi Kurnia (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2021)
Introduction: The current policy of pandemic caused changes the role of mothers in taking care of her children. However, verbal abuse among school-age children increase during COVID-19 pandemic. This study aimed to explain relationship between work stress level, education, and mother’s income with verbal abuse behavior among school-age children in Surabaya during COVID-19 pandemic.Method: This study used a correlational descriptive design with a cross-sectional approach. The study was conducted on mother who have school-age children. The number of samples was 73 mothers and 73 students of an elementary school aged 10-12 using the total sampling technique. The variables studied include mother’s work stress level, mother’s education, mother’s income, and verbal abuse on children. The instrument used was an online questionnaire (google form). The analysis used a statistical test of Spearman Rho (p ≤ 0,05).Results: The results of the study showed that there was a strong relationship between the mother’s work stress level and verbal abuse behavior among school-age children (p = 0.000; r = 0.559), there was a quite strong relationship between mother’s income and verbal abuse behavior among school-age children (p = 0.007; r = 0.314), while mother’s education not related to verbal abuse behavior among school-age children.Conclusions: Work stress level and mother’s income affect a mother’s belief that showed an intention to behave and finally caused verbal abuse behavior among school-age children.